Assessing the Use of Agricultural Lime for Pathogen Suppression in Bio-Slurry - Emmanuel Komagum Obong (Uganda Christian University, 2025)
At Mukono Boarding Primary School (MBPS), bio-slurry produced from a fixed-dome bio-digester that utilizes human excreta as feedstock, is daily discharged into the environment, and commonly applied to agricultural land by farmers without any form of pretreatment. This practice presents a significant environmental health risk and public health risk due to the presence of pathogenic organisms. This study assessed the use of agricultural lime for pathogen suppression in the bio-slurry generated at the MBPS bio-digester. Laboratory analysis of the bio-slurry showed that the concentrations of Escherichia coli and Ascaris lumbricoides eggs in the untreated bio-slurry exceeded the maximum permissible limits set by the National Environment Management Authority (NEMA). An optimum agricultural lime dosage of 60g/500mL was identified, and a seven day retention period was found to be most effective for pathogen suppression. Nutrient analysis confirmed that the agricultural lime treatment did not reduce the fertilizer value of the bio-slurry. A gravity-driven treatment system was developed, featuring a dosing chamber, baffle mix channel, and seven cascading retention chambers, offering a scalable and low-cost solution for safe bio-slurry discharge into the environment and use as a fertilizer.
Undergraduate